Morality at the Close of Humanism: Subject and Social in Habermas and Luhmann - Backhouse-Barber, Joseph (Sociologija. Mintis ir veiksmas, 2017)
This article is concerned with contemporary theories of epistemological uncertainty and their ramifications for our moral lives, and more specifically with how this uncertainty undermines the possibilities for conceiving of, and finding assurance in, humanistic morality. First, the uncertainties brought into knowledge by poststructuralism and Luhmann’s theory of observation are examined, particularly as they relate to the issue of reconciling the double moment of morality as an at once subjective and social phenomena. Next, Habermas’s important and influential work in this area is taken as exemplifying the limits of humanistic morality; it is argued that despite his interest and importance, Habermas’s work cannot support the weight of its own moral orientation, and that this is a direct consequence of the humanist structure of his thought, which cannot be reconciled with the paradoxical nature of the relationship between the subject and the social. Finally, some possibilities for maintaining humanism’s moral orientations through uncertainty are offered, primarily through the preservation of paradox, the acceptance of partiality, and the acknowledgement of the definitively incomplete nature of moral experience.